PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK - Suryani, Kadek Eka; Supriyono, Supriyono; Hidayat, Nurdin (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The problem in this study is whether there is an effect of the Talking Stick Learning Model on Economic Learning Outcomes in Class X Students in Even Semester of SMK Negeri 8 Bandar Lampung Academic Year 2018/2019. The purpose of this study was to determine the effect of the talking stick learning model on economic learning outcomes in class X students in the even semester of SMK Negeri 8 Bandar Lampung in the academic year 2018/2019. This study uses an experimental method, where research methods that require the writer to practice teaching directly on the subject under study using the talking stick learning model. The population in this study were 98 students of SMK Negeri 8 Bandar Lampung, amounting to 98 students in which the sample consisted of 2 classes namely X Accounting as an Experiment class which amounted to 34 people and X Sharia Banking as a control class of 32. After hypothesis testing on the two similarity tests - the average and the calculation of economic learning outcomes data using a statistical formula, then it is obtained 3.52 and at a significant level of 5%. This means that there is the influence of the talking stick learning model on economic learning outcomes in class X students in the even semester of SMK Negeri 8 Bandar Lampung in the academic year 2018/2019